2017
DOI: 10.1002/adma.201604493
|View full text |Cite
|
Sign up to set email alerts
|

Fully Solution‐Processed n–i–p‐Like Perovskite Solar Cells with Planar Junction: How the Charge Extracting Layer Determines the Open‐Circuit Voltage

Abstract: Fully solution-processed direct perovskite solar cells with a planar junction are realized by incorporating a cross-linked [6,6]-phenyl-C61-butyric styryl dendron ester layer as an electron extracting layer. Power conversion efficiencies close to 19% and an open-circuit voltage exceeding 1.1 V with negligible hysteresis are delivered. A perovskite film with superb optoelectronic qualities is grown, which reduces carrier recombination losses and hence increases V .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…20% with Voc=1.17 V. The third approach to reduce interfacial recombination is to introduce a very thin passivation layer between the perovskite and transport layers. 18,19,[34][35][36][37][38][39] For example, Zhang et al 35 showed that a very thin fullerene derivative (α-bis-PCBM) layer between the perovskite and the Spiro-OMeTAD HTL can reduce cell degradation and passivate defects at the perovskite/HTL interface, yielding a PCE of 20.8%, and Voc= 1.13 V. Similarly, Koushik et al 37 and Wang et al 39 used ultrathin layers of Al2O3 and poly(methyl methacrylate) (PMMA) respectively to passivate the perovskite/Spiro-OMeTAD interface, resulting in improved Voc (1.08V and 1.06V respectively) and reduced hysteresis. Recently,…”
Section: Introductionmentioning
confidence: 99%
“…20% with Voc=1.17 V. The third approach to reduce interfacial recombination is to introduce a very thin passivation layer between the perovskite and transport layers. 18,19,[34][35][36][37][38][39] For example, Zhang et al 35 showed that a very thin fullerene derivative (α-bis-PCBM) layer between the perovskite and the Spiro-OMeTAD HTL can reduce cell degradation and passivate defects at the perovskite/HTL interface, yielding a PCE of 20.8%, and Voc= 1.13 V. Similarly, Koushik et al 37 and Wang et al 39 used ultrathin layers of Al2O3 and poly(methyl methacrylate) (PMMA) respectively to passivate the perovskite/Spiro-OMeTAD interface, resulting in improved Voc (1.08V and 1.06V respectively) and reduced hysteresis. Recently,…”
Section: Introductionmentioning
confidence: 99%
“…[18] By a two-step sequential ethyl acetate interfacial processing, Fei and co-workers employed thiourea as additive in the perovskite precursor to effectively control the nucleation and subsequent crystal growth processes presenting compact microsized and monolithically grained perovskite films. [21][22][23] Although the above mentioned additive can achieve large-grained perovskite films, unfortunately, fabricating perovskite films with much more larger grain sizes along with lower trap densities using a novel additive is still a new challenge. Recently, Cai et al [20] introduced trimethylammonium chloride (TACl) as additive to prepare perovskite films.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the high‐efficiency, and therefore high V oc (>1 V), PSCs are fabricated with the conventional n–i–p structure, normally with planar or planar/mesoporous TiO 2 as an electron transport layer (ETL) deposited on a transparent electrode . The loss of V oc has been discussed in terms of interfacial recombination induced by top hole transport layers (HTLs), or by bottom ETL . Inverted devices, i.e., p–i–n architectures, comprising poly(3,4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) as bottom HTLs are associated with greater losses in photovoltage and their V oc is usually more than 100 mV lower than the V oc achieved with n–i–p devices .…”
Section: Introductionmentioning
confidence: 99%